TANTANGAN DAN PELUANG PENDIDIKAN DI ERA DIGITAL: Studi Di Mas Al-Washliyah 22 Tembung - Nur Aulia Alfitrah; Nuriza Dora; Toni Nasution (Al-Ikram : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Abstract: The development of the digital era has brought fundamental changes to the world of education, which have significant implications in terms of both challenges and opportunities. This study aims to determine the extent to which teachers can integrate technology, the challenges they face, and how adjustments are made to technology-based education curricula. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The research informants consisted of school principals, teachers, and students, thus providing diverse perspectives. The results showed that some teachers were able to use digital media such as PowerPoint, e-learning platforms, and online applications, but limitations in equipment, low digital literacy, and lack of training were significant obstacles. On the other hand, opportunities were opened up through the use of artificial intelligence, global access to information, and cross-cultural collaboration through digital platforms. This article contributes to the digital education literature by providing a critical analysis of the challenges and opportunities of education in the digital age, as well as offering practical recommendations for teachers, students, and education policymakers to respond more effectively to the changing times. Keywords: Challenges, Opportunities, Digital Education, Digital Literacy, Educational Technology